Red cell distribution width as a diagnostic marker in neonatal sepsis - Deka, Anupama; P., Aravind (International Journal of Contemporary Pediatrics, 2020)
Background: The early diagnosis of neonatal sepsis, a significant cause of neonatal morbidity and mortality still remains a challenge. Red-cell Distribution Width (RDW) vary significantly in conditions associated with inflammation and infection like sepsis. The study aims to find the normal range of RDW in healthy newborns and investigate the role of RDW in the early diagnosis of neonatal sepsis. Methods: This is a prospective observational study, 50 normal and 50 sepsis neonates were considered for the study. The neonatal sepsis group consisted of neonates with (i) Positive sepsis screen with/without clinical features of neonatal sepsis and/or (ii) Blood, urine or CSF culture positive or signs of pneumonia on chest x-ray. The mean RDW and the relationship between RDW and neonatal sepsis were analysed using appropriate statistical methods in SPSS-25 software. Results: Mean RDW (%) was significantly higher in sepsis neonates (18.59±1.28) than in normal newborns (16.21±1.35). RDW had statistical significance with CRP (C-Reactive Protein) in the sepsis group. RDW had significant relationship with the diagnosis of neonatal sepsis with a p value of 0.000. An RDW cut-off level of 17.25% had 86% sensitivity, 87% specificity, and 93.5% accuracy in diagnosing neonatal sepsis. Conclusions: RDW helps as a diagnostic test in the early diagnosis of neonatal sepsis.